PENGARUH KOMITMEN ORGANISASI DAN TINGKAT KECURANGAN TERHADAP INTENSI MELAKUKAN WHISTLE BLOWING DENGAN SIFAT MACHIAVELLIAN SEBAGAI PEMODERASI - Yunita Kurnia Shanti (Jurnal Akuntansi dan Pajak, 2022)
This study aims to examine the effect of organizational commitment and the level of fraud on the intention to do wishtle blowing with Machiavellian nature as a moderator at PT Jaya Konstruksi Manggala Pratama, Tbk. The population in this study were all permanent employees who worked at PT Jaya Konstruksi Manggala Pratama, Tbk as many as 45 people. The sampling method using a saturated sample, namely the use of the entire population without having to draw a research sample as the unit of observation, is referred to as the saturated or census technique. The number of questionnaires as many as 45 were distributed and obtained a sample of 32 respondents who returned and could be tested. Methods of data analysis using multiple linear regression and MRA. The results of this study indicate that organizational commitment has a significant effect on the intention to do whistle blowing. The two levels of fraud have no effect on the intention to do whistle blowing. The three organizational commitments and the level of fraud simultaneously affect the intention to do whistle blowing. The four Machiavellian traits are not able to moderate the effect of organizational commitment on the intention to do whistle blowing. The five Machiavellian traits are not able to moderate the influence of the level of fraud on the intention to do whistle blowing. The six Machiavellian traits are able to moderate the effect of organizational commitment and the level of fraud simultaneously on the intention to do whistle blowing. This shows that the large or small value and form of existing fraud still needs to be reported as an action that can harm the company in the short and long term, regardless of whether the individual expects a reward in the form of money or the like but rather on loyalty and commitment to the organization.